Characterization of Fenoxaprop-P-Ethyl–Resistant Junglerice (Echinochloa colona) from Mississippi. Issue 4 (December 2016) - Wright, Alice A.; Nandula, Vijay K.; Grier, Logan; Showmaker, Kurt C.; Bond, Jason A.; Peterson, Daniel G.; Ray, Jeffery D.; Shaw, David R.
Abstract : A population of junglerice from Sunflower County, MS, exhibited resistance to fenoxaprop-P-ethyl. An 11-fold difference in ED50 (the effective dose needed to reduce growth by 50%) values was observed when comparing the resistant population (249 g ae ha –1 ) with susceptible plants (20 g ae ha –1 ) collected from a different field. The resistant population was controlled by clethodim and sethoxydim at the field rate. Sequencing of the acetyl coenzyme A carboxylase, which encodes the enzyme targeted by fenoxaprop-P-ethyl, did not reveal the presence of any known resistance-conferring point mutations. An enzyme assay confirmed that the acetyl coenzyme A carboxylase in the resistant population is herbicide sensitive. Further investigations with two cytochrome P450 inhibitors, malathion and piperonyl butoxide, and a glutathione- S -transferase inhibitor, 4-chloro-7-nitrobenzofurazan, did not indicate involvement of any metabolic enzymes inhibited by these compounds. The absence of a known target-site point mutation and the sensitivity of the ACCase enzyme to herbicide show that fenoxaprop-P-ethyl resistance in this population is due to a non–target-site mechanism or mechanisms.